2008
DOI: 10.1510/icvts.2007.158451
|View full text |Cite
|
Sign up to set email alerts
|

A study assessing the potential benefit of continued ventilation during cardiopulmonary bypass

Abstract: It has been suggested that maintaining ventilation during bypass might reduce lung injury, which is a common complication of cardiac surgery. In order to assess this, a study is being undertaken to examine the effect upon a number of parameters that may be indicative of lung injury, of continued ventilation compared with discontinued ventilation whilst on bypass. The following parameters have been assessed: extravascular lung water, static and dynamic compliance, ratio of left atrial/right atrial white blood c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
32
0
2

Year Published

2010
2010
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(36 citation statements)
references
References 13 publications
2
32
0
2
Order By: Relevance
“…They all failed to document a significant difference with regard to ΔA–aO 2 . Only John et al 21 reported less extravascular lung fluid accumulation and a decreased period of ventilation.…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…They all failed to document a significant difference with regard to ΔA–aO 2 . Only John et al 21 reported less extravascular lung fluid accumulation and a decreased period of ventilation.…”
Section: Discussionmentioning
confidence: 97%
“…Gagnon et al 4 determined a tidal volume of 3 ml/kg during CPB and John et al 21 5 ml/kg. Boldt et al 22 continued normal ventilation during CPB.…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this, another experimental study showed that continuous ventilation during CPB provided no significant improvement in pulmonary vascular resistance, respiratory index, or oxygen tensions [91]. More recently, John et al [92] showed in their randomized study that continued ventilation during CPB by tidal volume of 5 ml/Kg resulted significant smaller extravascular lung water and a shorter extubation-time. To date, the evidence for clear benefits of maintaining ventilation alone during CPB is inconsistent, with most studies showing no significant preservation of lung function [5,88].…”
Section: Methodology and Strategy For Management Of Lung Dysfunction mentioning
confidence: 99%
“…Intraoperative use of inhaled pulmonary vasodilators has been described, and showed to improve cardiac output and decrease pulmonary artery pressures in patients undergoing cardiac surgery . Intraoperative ventilation while on cardiopulmonary bypass has also been described and shown lead to lower levels of postoperative lung water, less pulmonary inflammation, quicker time to extubation . To our knowledge, this is the first study to describe the elective application of both iEpo with continuous intraoperative low tidal volume ventilation while on CPB during surgery for complex cases of valvular IE.…”
Section: Discussionmentioning
confidence: 99%